О границах применимости некоторых методов решения задачи переноса излучения в рассеивающих средах - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А.; Кутлин А. П. (Томск, 1985)
Деп. в ВИНИТИ 30.07.85, № 5595-85